2017
DOI: 10.21475/ajcs.17.11.02.p240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of foliar nickel (Ni) application on mineral nutrition status, urease activity and physiological quality of soybean seeds

Abstract: Nickel (Ni) at low concentrations is an essential micronutrient for higher plants. Nickel is a cofactor of the enzyme urease and plays a critical role in the germination of seeds. This study aims to evaluate the effect of foliar Ni application on mineral nutrition status, urease activity and the physiological quality of soybean seeds. The study was conducted using different levels of Ni (0, 10, 20, 40, 60, 80 and 100 g ha -1 ) were applied in the presence or absence (0 or 75 g i.a. ha -1 ) of the fungicide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The worldwide average concentration of Ni in natural soils is 22 mg kg −1 [8,9] and has been reported up to 26.4 g kg −1 in soil and 0.3 mg L −1 in water [10,11]. Its toxicity symptoms appear between 0.19 and 0.85 mM kg −1 plant dry biomass [12]. Nickel toxicity inhibits the enzymatic activity, such as the Calvin cycle and chlorophyll biosynthesis which decreases photosynthetic efficiency in plants [13].…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide average concentration of Ni in natural soils is 22 mg kg −1 [8,9] and has been reported up to 26.4 g kg −1 in soil and 0.3 mg L −1 in water [10,11]. Its toxicity symptoms appear between 0.19 and 0.85 mM kg −1 plant dry biomass [12]. Nickel toxicity inhibits the enzymatic activity, such as the Calvin cycle and chlorophyll biosynthesis which decreases photosynthetic efficiency in plants [13].…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, the average concentration of Ni in soils is 22 mg kg À1 , while the maximum Ni has been reported at 26.40 g kg À1 in the soil and 0.30 mg L À1 in water (Amjad et al, 2019). However, the threshold level for Ni toxicity in plants is found to be between 0.20 and 0.85 mM kg À1 dry weight (DW) (de Queiroz Barcelos et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This result contradicts other similar studies. In the work of Barcelos et al (2017), foliar application of a Ni-single solution was made, and they observed a linear increase in leaf N concentration. Although the work of Freitas et al (2018) having used Ni fertilization in soybean cultivated soil, there was also an increase in leaf N concentration, among other increases in N metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…After urease action, N is quickly metabolized and incorporated into amino acids and amides. The urease foliar activity is very important when N comes from foliar applications, and although this enzyme helps in the efficient N assimilation, ammonia toxicity can occur when its activity is too high (BARCELOS et al, 2018;BARCELOS et al, 2017;BOER et al, 2014;POLACCO et al, 2013).…”
Section: Introductionmentioning
confidence: 99%